Atividades comerciais e de serviços e centralidade intraurbana em Presidente Prudente, São Paulo, Brasil: Commercial and service activities and intra-urban centrality in Presidente Prudente, São Paulo, Brazil (Élisée - Revista de Geografia da UEG, 2022)
Abstract: The location of commercial and service activities in the year 2010 in the city of Presidente Prudente – SP is the central theme is this article. Therefore, we used as methodological procedures the construction of a database from the National Register of Addresses for Statistical Purposes (CNEFE) and the National Classification of Economic Activities (CNAE). CNEFE and CNAE made it possible to produce cartographic representations that supports our analysis of the center and intra-urban centrality in Presidente Prudente – SP. In view of the results obtained with the methodological procedures, we can observe the presence of a large concentration of commercial and service establishments in the main center. However, new areas also showed concentrations, mainly due to shopping centers, which sometimes reinforce the centrality exercised by the main center, sometimes configure new central area.Keywords: center; centrality; multi(poly)centrality; shopping centers; Presidente Prudente – SP;